ADOBE FLASH UNTUK MENDUKUNG PEMBELAJARAN - Supriyadi S (Jurnal Komunikasi, 2016)
Learning to use computer animation to allow students to learn in a dynamic and interactive. Many of the benefits derived from the use of computer media as a learning tool. Adobe Flash is a standard application program used to create animation vector and bitmap which is amazing for the purposes of making a web site that is interactive and dynamic. This application is implemented as a medium of learning. The message conveyed through the media, in the form of content or teaching materials that must be accepted by the students, by using one or a combination of several of their sensory organs. Even better, when all of the sensing devices owned able to receive the message content being delivered. This paper is a study piustaka and try to express that creativity is needed in this case the animation tools in the process of teaching belaar be more easily understood by students.Keywords: adobe flash, learning.